2015
DOI: 10.3382/ps/pev132
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of true ileal phosphorus digestibility in meat and bone meal for broiler chickens

Abstract: An experiment was conducted to estimate true ileal phosphorus (P:) digestibility of 3 meat and bone meal samples (MBM-1, MBM-2: , and MBM-3:) for broiler chickens. Four semipurified diets were formulated from each sample to contain graded concentrations of P. The experiment was conducted as a completely randomized design with 6 replicates (6 birds per replicate) per dietary treatment. A total of 432 Ross 308 broilers were assigned at 21 d of age to the 12 test diets. The apparent ileal digestibility coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
4
10
2
1
Order By: Relevance
“…The SBM diets 1 to 3 also yielded higher excreta P retention values of 49 to 63% than the MBM diets 7 to 9 (32–39%). The apparent ileal P digestibility values for MBM of 66 to 79% are slightly higher than values from the study by Mutucumarana et al. (2015a) who reported apparent ileal P digestibility values for 3 samples of MBM ranging from 49 to 69%.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations
“…The SBM diets 1 to 3 also yielded higher excreta P retention values of 49 to 63% than the MBM diets 7 to 9 (32–39%). The apparent ileal P digestibility values for MBM of 66 to 79% are slightly higher than values from the study by Mutucumarana et al. (2015a) who reported apparent ileal P digestibility values for 3 samples of MBM ranging from 49 to 69%.…”
Section: Resultscontrasting
confidence: 77%
“…The results of the latter study and the present study are in contrast to several earlier growth/bone ash studies that concluded that the P in animal products are highly or totally available for poultry ( Waldroup et al., 1965 ; NRC, 1994 ; Sell and Jeffrey, 1996 ). Thus, the results of Experiment 1 of the present study, Dilger and Adeola (2006) , and Mutucumarana et al. (2015a) suggest that SBM, a plant-based feed ingredient, has apparent P digestibility equal to or higher than that of MBM, an animal by-product, when using a prececal or ileal P digestibility assay.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…Geralmente são fonte de proteína de alta qualidade e digestibilidade que podem auxiliar no balanço de aminoácidos exigidos pelos animais, além de excelentes fontes de fósforo disponível e outros minerais. Entretanto, apresentam grande variabilidade em sua composição nutricional (HENDRIKS et al, 2002;MUTUCUMARANA et al, 2015), são potencialmente suscetíveis á oxidação (NOLLET; TOLDRÁ, 2011) e à contaminação microbiana (DAVIES;HINTON, 2000;SAPKOTA et al, 2007). As preocupações com a presença de microrganismos nas farinhas não se restringem aos danos causados aos animais, mas aos impactos dessas contaminações na saúde humana (SAPKOTA et al, 2007).…”
Section: Introductionunclassified